MEHETABEL’S TRAITS AGAINST THE NEGATIVE STEREOTYPES OF ELDERLY PORTRAYED IN DOROTHY CANFIELD FISHER’S SHORT STORY THE BEDQUILT - YUNIAR, MADARINA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Short story is a brief fictional prose narrative that is shorter than a novel and usually deals with only a few characters. Short story becomes a media to reveal social phenomena in a society. One of the social phenomena is about elderly life that is shown in The Bedquilt short story by Dorothy Canfield Fisher. The Bedquilt portrays Mehetabel as the main character traits against the stereotypes of elderly.To carry out the study, the writer applies sociological perspective by using the theory of Social Gerontology. Social Gerontology is the field of study that concern to the social construction in the society around aging. The disengagement and activity theories are applied along with the stereotypes of elderly.The result of the study shows that Mehetabel reflects the traits against the stereotypes of elderly. She is able to break out the stereotypes that most elderly are lonely, unproductive, unimportant, cannot learning, and underestimating. She is not lonely even though she does not have spouse who can give her affection and attention. She enjoys her late adulthood by quilting the bedquilt. Her family still can take the advantages of her existence to do the household labors and she can create the beautiful quilting pattern. Her willing to create the quilt is so strong, although her finger skill has already declined because the pneumonia that attacks her. Her wonderful quilt leads her to be a succesful elderly that make her house to be an important and interesting tourism object. She also has wisdom and spirituality because she is not angry with her family treatments and she understands about the family condition.From the result of her traits, she can be categorized as an successful elderly. It is hoped for the next researchers to conduct a deeper research which explores more about the psychological aspect and how a social change can affects psychological condition of the elderly.Key Words: Mehetabel, Traits, Against, Negative Stereotypes, Elderly, The Bedquilt.